Determinants of utilisation rates of preventive health services: evidence from Chile - Elena S. Rotarou; Dikaios Sakellariou (BMC, 2018)
Abstract Background Preventive health services play a vital role in population health. However, access to such services is not always equitably distributed. In this article, we examine the barriers affecting utilisation rates of preventive health services, using Chile as a case study. Methods We conducted a cross-sectional study analysing secondary data from 206,132 Chilean adults, taken from the 2015 National Socioeconomic Characterisation Survey of the Government of Chile. We carried out logistic regressions to explore the relationship between the dependent variable use of preventive services and various demographic and socioeconomic variables. Results Categories more likely to use preventive services were women (OR=1.16; 95%CI: 1.11-1.21) and inactive people (OR=1.41; 95%CI: 1.33-1.48). By contrast, single individuals (OR= 0.85 ; 95%CI: 0.80-0.91) and those affiliated with the private healthcare provider (OR= 0.89; 95%CI: 0.81-0.96) had fewer odds of undertaking preventive exams. Conclusions The findings underline the necessity of better information campaigns on the availability and necessity of preventive health services, addressing health inequality in accessing health services, and tackling lifestyle-related health risks. This is particularly important in countries - such as Chile - characterised by high income inequality and low utilisation rates of preventive health services.